How do You Display 3D Cultural Heritage Data in Museums? - Inoue, Hayata; Umemura, Ayako; Hayakawa, Hirono; Hori, Ryo; Endo, Mamoru; Urat, Mayu; Yasuda, Takami; Kajiwara, Yoshimitsu (The Indonesian Journal of Social Studies, 2024)
In this paper, we present “Culpticon,” a project developed at Japan’s Nagoya University to present three-dimensional (3D) cultural heritage data in museums. Culpticon represents a unique response to the challenges facing social education on cultural heritage in museums. Our project’s primary objective is to facilitate seamless museum access via the World Wide Web. Recognizing the critical issues that Japanese museums are facing is essential to understand this project’s background. Decreasing visitor interest in cultural heritage has resulted in severe financial constraints, which Japan’s economic difficulties since the 1990s have further exacerbated due to diminishing administrative support. This has put our cultural heritage’s preservation at risk. To address these challenges, our approach focuses on engaging the public directly with museums and utilizing education as a form of entertainment. Concentrating on smartphone accessibility, we have devised a user-friendly method that enables users to explore 3D heritage data in museum collections. One of the system’s key features is the ability to provide a comprehensive view of cultural heritage data from any angle. Furthermore, it is accessible from any location with an Internet connection, ensuring that information on cultural heritage is readily available to the public. Thus, Culpticon represents a significant step toward democratizing access to cultural heritage. Bridging the gap between museums and the public enhances social education and reinforces the preservation of our invaluable cultural legacy.